2019
DOI: 10.1111/fwb.13440
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the life cycle of monogonont rotifers: Commitment to sex and emergence from diapause

Abstract: A review of research on life‐cycle events in field and laboratory populations of monogonont rotifers shows that there is great variation at multiple levels: (1) degree of sexual dimorphism; (2) occurrence and timing of sex; (3) propensity for sex during sexual periods; (4) factors controlling initiation of sex; and (5) timing and extent of emergence from diapause. There is no regular pattern where: (1) fertilised resting eggs hatch to start the growing season; (2) populations develop via female parthenogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 163 publications
(293 reference statements)
2
20
0
Order By: Relevance
“…Hypoxia studies in the rotifer Brachionus manjavacas, an aquatic invertebrate suitable for aging studies, demonstrated a mean lifespan extension of 107% when continuously exposed to 1.6% atm. Hypoxic conditions in this organism increased reproductive success by twofold and conferred cytoprotection against stress (Snell et al, 2019). This observation supports previous studies on rotifer communities and their adaptation to high salinity and low oxygen (Esparcia et al, 1989).…”
Section: Hypoxic Adaptation Potentially Promotes Longevitysupporting
confidence: 90%
“…Hypoxia studies in the rotifer Brachionus manjavacas, an aquatic invertebrate suitable for aging studies, demonstrated a mean lifespan extension of 107% when continuously exposed to 1.6% atm. Hypoxic conditions in this organism increased reproductive success by twofold and conferred cytoprotection against stress (Snell et al, 2019). This observation supports previous studies on rotifer communities and their adaptation to high salinity and low oxygen (Esparcia et al, 1989).…”
Section: Hypoxic Adaptation Potentially Promotes Longevitysupporting
confidence: 90%
“…Our findings are consistent with earlier studies that found density to be an important factor influencing the shift from asexual to sexual reproduction in cyclical parthenogens like Daphnia and rotifers (Berg et al, 2001;Gilbert, 2020;Haltiner et al, 2020;Larsson, 1991;Stelzer & Snell, 2003;Stross & Hill, 1965). One possible explanation for this association is that, in many cyclical parthenogens, sexual reproduction is associated with the production of long-lasting resting…”
Section: Discussionsupporting
confidence: 93%
“…stages, meaning sexual reproduction may serve as a means of temporal dispersal when faced with strong competition in dense populations Gilbert, 2020). High densities also reduce the relative costs of sexual reproduction; as populations approach carrying capacity, asexual reproduction is less beneficial, reducing the opportunity costs of sexual reproduction (Burt, 2000;.…”
Section: Discussionmentioning
confidence: 99%
“…The switch from asexual to sexual reproduction in facultatively sexual animals can be highly variable within and between species (Tessier and C aceres 2004, Navarro et al 2013, Franch-Gras et al 2017, Ryan and Miller 2019. For instance, in freshwater invertebrates such as water fleas, monogonont rotifers or freshwater hydra clonal lineages frequently differ in sexual propensity such that some genotypes show no sexual investment at all, while in others all individuals within a clonal lineage invest in sex in response to specific environmental cues (Tessier and C aceres 2004, T€ ok€ olyi et al 2017b, Gilbert 2020. Central to research on facultatively sexual organisms is to identify factors that drive this variation.…”
Section: Introductionmentioning
confidence: 99%